2012
DOI: 10.32800/abc.2012.35.0267
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive genetic approaches for estimation of ungulate population size: a study on roe deer (Capreolus capreolus) based on faeces

Abstract: Estimating population size is particularly difficult for animal species living in concealing habitats with dense vegetation. This is the case for roe deer as for many other ungulates. Our objective was to develop a non–invasive genetic capture–mark–recapture approach based on roe deer faeces collected along transects. In a pilot study, we collected 1,790 roe deer faeces during five sampling days in a forested study area in south western Germany. We extracted DNA from 410 of these samples and carried out micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 42 publications
3
7
0
Order By: Relevance
“…Further, we applied a strict rule in detecting homozygotes to ensure a minimum allelic dropout rate and increase the probability of consensus homozygous genotypes to be true homozygotes (Taberlet et al., 1996). The dropout rate across loci and years of approximately 20% is in accordance with observed dropout rates in other NiG studies (e.g., Ebert, Sandrini, Spielberger, Thiele, & Hohmann, 2012; Hansen, Ben‐David, & McDonald, 2008). While such restrictive genotype calling limited the overall genotyping success rate, it allowed us to keep the error rate at a reasonably low level.…”
Section: Discussionsupporting
confidence: 89%
“…Further, we applied a strict rule in detecting homozygotes to ensure a minimum allelic dropout rate and increase the probability of consensus homozygous genotypes to be true homozygotes (Taberlet et al., 1996). The dropout rate across loci and years of approximately 20% is in accordance with observed dropout rates in other NiG studies (e.g., Ebert, Sandrini, Spielberger, Thiele, & Hohmann, 2012; Hansen, Ben‐David, & McDonald, 2008). While such restrictive genotype calling limited the overall genotyping success rate, it allowed us to keep the error rate at a reasonably low level.…”
Section: Discussionsupporting
confidence: 89%
“…Non-invasive population size estimation approaches have to date been applied for several ungulate species, amongst them different Odocoileus species (e.g. Brinkman et al (2011) for Sitka black-tailed deer Odocoileus hemionus sitkensis in Alaska; Goode et al (2014) and Brazeal et al (2017) for mule deer O. hemionus and O. h. columbianus), argali sheep Ovis ammon (Harris et al 2010), Sonoran pronghorn Antilocapra americana sonoriensis (Woodruff et al 2016), roe deer Capreolus capreolus (Ebert et al 2012) and mountain goats Oreamnos americanus (Poole et al 2011). For red deer, a first evaluation of the technical background for non-invasive population monitoring was carried out in a pilot study (Valière et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic sex ratio analyses within the study area revealed a higher percentage of females to males roe deer within the population of the central Palatinate Forest (2011: 1 ♂ : 1.4 ♀, Ebert et al (2012b)). Hence, the sex ratio of the standing roe deer population in our study area does not reflect the sex ratio of the lynx prey to such an extent.…”
Section: Discussionmentioning
confidence: 87%
“…In 2012, wild boar density within the centre of the Palatinate Forest was estimated at around 4.5-5.0 individuals km -² (Ebert et al 2012a). Deer densities were estimated at around 3.3 red deer km -² (Ebert et al 2021) and 5.9 roe deer km -² (Ebert et al 2012b) within the same area. For the rest of the whole study area, only hunting bag data exists, which is currently only geographically assigned within state-managed parts of the forest (Fig.…”
Section: Study Areamentioning
confidence: 99%